Experiences of Polish Forced Laborers from Łódź Employed for Telefunken in Ulm in Years 1944–1945 with Consideration of Medical Care - Steger, Florian; Orzechowski, Marcin (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2020)
In years 1944–1945, more than 1.400 girls and young women from the Polish city of Łódź were displaced to Ulm in Germany and forced to work there. During their stay, the girls had to endure severe living conditions, and were exposed to diseases. Through deprivation and exploitation, forced laborers for Telefunken were condemned to daily suffering. Such a system of exploitation was symptomatic for the late phase of the war, during which efforts towards increasing war production came at the cost of sacrificing the health of foreign workers. The goal of this paper is a historical reappraisal of their experiences, with special attention paid to the medical care that they received. We present the extent of the medical treatment provided for the laborers, the aim of which was only the restoration of their further ability to work.